Simulator Fungsi Dummy Load Menggunakan Kontrol Komputerise - Teguh Budi Prayogo (Sekolah Tinggi Teknik PLN, 2019)
ABSTRACT Dummy Load is used as an imitation load on the loading practice on a PLTD or PLTS generator. The existing dummy load currently installed is the conventional resistive dummy load type which is dominant at active power. The problem is that the dummy load does not yet represent the actual actual load condition, namely the RLC load. The power consumption by the dummy load is controlled by varying the firing angle ‘α’ of the thyristor- pair [1] Therefore it is necessary to improve the function of the dummy load by improving and developing the design and construction. The design of the construction improvement and development will be carried out on the main components and the digital computerized monitoring and control system for its operation. In this paper, the microcontroller-based electronic load controller (ELC) as a voltage and frequency stabilizer is designed when the dummy load is operated. This tool can prevent damage due to the frequency and output voltage of the distribution system. The result of the reconstruction is to make the PLTD / PLTS dummy load that has the ability of dummy load RLC balanced load / unbalanced load for operating loading practices, where in operation it uses a digital computerized control system that can programmed manually / auto and has a facility / feature event recorder. Keywords: Dummy Load, RLC, Function Enhancement, Computer Control System